2012
DOI: 10.1590/s1806-66902012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Umidade do solo e doses de potássio na cultura da soja

Abstract: Resumo -Os solos tropicais, normalmente pobres em potássio (K), quando cultivados com soja (Glycine max L.) demandam adubação potássica para obtenção de produtividades satisfatórias. Objetivou-se com este trabalho avaliar o efeito de doses de K e níveis de umidade do solo nos componentes de produção da soja. O experimento foi realizado em casa de vegetação e os tratamentos foram dispostos em um delineamento em blocos casualizados em esquema fatorial (5 x 3), com cinco repetições. Um vaso com 5 dm 3 de solo com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
11
0
8
Order By: Relevance
“…All doses provided a greater seed weight if compared to control, especially the 90 kg ha -1 K 2 O dose. These data differ from those experienced by Gonçalves et al (2010), however, corroborate those obtained by Serafim et al (2012). It is possible to observe that the equation describing the behavior of the variable thousand seeds weight to K application follows the same trend of the equations that describe the accumulation of biomass and index of grain harvest (IGH), since the last one expresses the crop efficiency of converting biomass into grain productivity.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…All doses provided a greater seed weight if compared to control, especially the 90 kg ha -1 K 2 O dose. These data differ from those experienced by Gonçalves et al (2010), however, corroborate those obtained by Serafim et al (2012). It is possible to observe that the equation describing the behavior of the variable thousand seeds weight to K application follows the same trend of the equations that describe the accumulation of biomass and index of grain harvest (IGH), since the last one expresses the crop efficiency of converting biomass into grain productivity.…”
Section: Resultssupporting
confidence: 79%
“…The number of grains per pod is influenced by a genetic characteristic of this cultivar and by the nutritional status of the plant, thus explaining the lack of effect of K doses in this study, since the levels of K in soil were found within the range considered as high for the Savannah region. The effect of the absence of K application could, probably, manifest at low availability in the soil, being able in a K deficiency situation, to cause an increase in the number of empty lobes, as verified (Serafim et al, 2012).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…, resultando em maior produtividade. O mesmo fato foi verificado por Petter et al (2012) e Serafim et al (2012), que, testando adubação potássica na soja, obtiveram respostas positivas para a massa de grãos e rendimento de grãos em função da utilização de K.…”
Section: Resultsunclassified
“…Serafim et al (2012) observaram aumento no rendimento e no peso específico das sementes, em resposta à adubação com esse nutriente.…”
Section: Methodsunclassified